Dismemberment and mutilation of victims postmortem: a guide for the medical legal death investigator - Caiano, Tara Louise (2012)
Thesis (M.S.)--Boston University.The main goal of medical legal death investigators is to determine the time and cause of death. This becomes more difficult when presented with a victim that has been mutilated, dismembered, and scattered across multiple crime scenes. Perpetrators will dismember their victims for many reasons including concealing the identity of the victim, disposing of the body, and retaining body parts as reminders of the crime. The way the crime scene appears, how the victim is dismembered, and the parts of the body that remain are crucial in determining the cause of death, the identity of the victim and the perpetrator. There are four different categories of dismemberment which all have implications about the perpetrator including their identity, mental state during the commission of the crime, and motive. The history of dismemberment was studied and found to have significance in modern day crimes. Tool mark identification was also researched to determine weapons used during the crime and to give clues as to how the victims were dismembered. Crimes of this nature have not been studied to determine trends or statistics that would aid in solving them. The majority of the dismemberment crimes studied involved male perpetrators (76% ). When broken down into age brackets, a similar distribution was found amongst men and women. The category of dismemberment that occurred in 69% of the cases was defensive mutilation, which is the result of a perpetrator attempting to hinder the victim's identity. With the combination of case studies and forensic psychology research, an approach was validated to be used by medical legal death investigators in cases involving dismemberment